Odor Perception in Children with Autism Spectrum Disorder and its Relationship to Food Neophobia - Luisier, Anne-Claude; Petitpierre, Genevieve; Ferdenzi, Camille; Clerc Bérod, Annick; Giboreau, Agnes; Rouby, Catherine; Bensafi, Moustafa (Frontiers in Psychology, 2015)
Atypical sensory functioning in Autism Spectrum Disorder (ASD) has been well documented in the last decade for the visual, tactile and auditory systems, but olfaction in ASD is still understudied. The aim of the present study was to examine whether children with ASD and neuro-typically (NT) developed children differed in odor perception, at the cognitive (familiarity and identification ability), sensorimotor (olfactory exploration) and affective levels (hedonic evaluation). Because an important function of the sense of smell is its involvement in eating, from food selection to appreciation and recognition, a potential link between odor perception and food neophobia was also investigated. To these ends, 10 children between 6 and 13 years old diagnosed with ASD and 10 NT control children were tested. To compare performance, 16 stimuli were used and food neophobia was assessed by the parents on a short food neophobia scale. Results revealed that (i) significant hedonic discrimination between attractive and aversive odors was observed in NT (p=0.005; d=2.378) and ASD children (p=0.042; d=0.941), and (ii) hedonic discrimination level was negatively correlated with food neophobia scores in ASD (p=0.007) but not NT children. In conclusion, this study offers new insights into odor perception in ASD children, highlighting a relationship between odor hedonic reactivity and eating behavior. This opens up new perspectives on both (i) the role of olfaction in the construction of eating behavior in ASD children, and (ii) the measurement and meaning of food neophobia in this population.